Family impact of pemphigus disease in an Iranian population using the Family Dermatology Life Quality Index - S. Zahra Ghodsi, MD; Arefeh Asadi, MD; Narges Ghandi, MD; Kamran Balighi, MD; Hamidreza Mahmoudi, MD; Robabeh Abedini, MD; Maryam Ghiasi, MD; Vahideh Lajevardi, MD; Cheyda Chams-Davatchi, MD; Maryam Daneshpazhooh, MD (Wolters Kluwer, 2020)
Background: Pemphigus vulgaris (PV) is a rare but seriously disabling disorder of the skin and mucous membranes that can gravely impact the quality of life (QoL) of patients. Objective: The aim of the present study was to identify how family members of patients with PV are affected by the disease. Methods: A total of 118 patients with confirmed PV and one of their family members (caregivers) were enrolled in the study. To calculate disease severity, the Autoimmune Bullous Skin Disorder Intensity Score was used. The Persian version of the Dermatology Life Quality Index (DLQI) questionnaire was used to evaluate the QoL of patients and the Family Dermatology Life Quality Index (FDLQI) to evaluate the QoL of caregivers. Results: The mean age of patients was 43.14 ± 12.5 years. Ninety patients (76.3%) were female. Eighty-one patients (68.6%) had the mucocutaneous phenotype and 37 cases (31.4%) the mucosal phenotype. The DLQI score was 10.1 ± 7.1 for patients. The DLQI score was higher for patients with the mucocutaneous phenotype (11.8 ± 7.5) than those with the mucosal phenotype (6.4 ± 4.9; p < .001). QoL was significantly affected by disease severity. FDLQI score was 13 ± 7 for caregivers, and was significantly higher in older caregivers and married ones. There was a positive correlation between patients' admission frequencies and FDLQI score. FDLQI score was also significantly affected by the Autoimmune Bullous Skin Disorder Intensity Score of patients' disease severity. The QoL of patients and their caregivers showed a significant positive correlation. Conclusion: The QoL of patients and their families are impaired significantly, and is considerably prominent in the mucocutaneous phenotype of PV and more severe forms. Limitation: Pemphigus Disease Area Index (PDAI) and Autoimmune Bullous Disease QoL (ABQoL) were not used in this study.